40.8k views
4 votes
Which is not an equation of the line going through (3, -6) and (1,2)

Which is not an equation of the line going through (3, -6) and (1,2)-example-1
User Anfernee
by
5.9k points

2 Answers

3 votes
Answer is A.
You can find the answer by plugging in X and Y to the equations




User Wurde
by
5.3k points
0 votes

Answer:

The correct option is A) y - 1 = -4(x-2) is an equation of the line going through (3, -6) and (1,2)

Explanation:

we have to find which is not an equation of the line going through (3, -6) and (1,2)

Put (3, -6) and (1,2) in Part A)

y - 1 = -4(x-2)

for (3, -6)

-6 - 1 = -4(3-2)

-7 ≠ -4

for (1,2)

2 - 1 = -4(1-2)

1 = -4(-1)

1 ≠ 4

This is not an equation of the line going through (3, -6) and (1,2)

Put (3, -6) and (1,2) in Part B)

y - 2 = -4(x-1)

for (3, -6)

-6 - 2 = -4(3-1)

-8 = -8

for (1,2)

2 - 2 = -4(1-1)

0= 0

This is an equation of the line going through (3, -6) and (1,2)

Put (3, -6) and (1,2) in Part C)

y + 6 = -4(x-3)

for (3, -6)

-6 + 6 = -4(3-3)

0 = 0

for (1,2)

2 + 6 = -4(1-3)

8= 8

This is an equation of the line going through (3, -6) and (1,2)

Put (3, -6) and (1,2) in Part D)

y = -4x + 6

for (3, -6)

-6 = -4(3) + 6

-6 = -6

for (1,2)

2 = -4(1) + 6

2 = 2

This is an equation of the line going through (3, -6) and (1,2)

Hence, The correct option is A) y - 1 = -4(x-2) is an equation of the line going through (3, -6) and (1,2)

User Cruel
by
5.7k points